The Olfactory Mosaic: Bringing an Olfactory Network Together for Odor Perception. (March 2017) - Courtiol, Emmanuelle; Wilson, Donald A.
Olfactory perception and its underlying neural mechanisms are not fixed, but rather vary over time, dependent on various parameters such as state, task, or learning experience. In olfaction, one of the primary sensory areas beyond the olfactory bulb is the piriform cortex. Due to an increasing number of functions attributed to the piriform cortex, it has been argued to be an associative cortex rather than a simple primary sensory cortex. In fact, the piriform cortex plays a key role in creating olfactory percepts, helping to form configural odor objects from the molecular features extracted in the nose. Moreover, its dynamic interactions with other olfactory and nonolfactory areas are also critical in shaping the olfactory percept and resulting behavioral responses. In this brief review, we will describe the key role of the piriform cortex in the larger olfactory perceptual network, some of the many actors of this network, and the importance of the dynamic interactions among the piriform-trans-thalamic and limbic pathways.